TINGKAT PENGETAHUAN DAN DUKUNGAN KELUARGA TERHADAP PERAWATAN LANJUTAN PADA PASIEN PASCA STROKE - Fadli Syamsuddin; Pipin Yunus (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
This research is carried out in Puskesmas Tilamuta working area, district Boalemo. The purpose of this research is to analyze the correlation of the level of knowledge and family support toward extended care of patient with stroke in Puskesmas Tilamuta. The type of the research is observational analysis with cross sectional study approach. The sample of the research is a family with member that has ha stroke in Puskesmas Tilamuta working area which consist of 32 people. Based on the univariat result, respondents with high level of knowledge 23 people (71,9 %), sample with more support is 19 respondents (59,4 %), and 24 respondents (75 %) that gives the care. Based on the bivariat analysis using chi square obtained the P with α 0,05 for knowledge p=0,01, support p=0,02. Based on the result of the research, it can be concluded that there is a correlation of the level of of knowledge and family support toward extended care of patient with stroke in Puskesmas Tilamuta.